Cigarette Smoking and Longitudinal Associations With Blood Pressure: The CARDIA Study - Luehrs, Rachel E. (J Am Heart Assoc, 2021)
BACKGROUND: The associations of chronic cigarette smoking with blood pressure (BP) remain mixed. It is unclear whether a lack of examination of racial differences contributed to the mixed findings in previous studies. Black smokers metabolize nicotine at a slower rate than White smokers and racial discrimination contributes to nicotine dependence and higher BP among Black smokers. METHODS AND RESULTS: We studied the association between cigarette smoking and longitudinal (30‐year) changes in systolic BP, diastolic BP, and pulse pressure (PP) in 4786 Black and White individuals from the CARDIA (Coronary Artery Risk Development in Young Adults) study using repeated‐measures regression models. Neither systolic BP, nor diastolic BP differed between Black consistent smokers compared with Black never smokers, although Black consistent smokers had higher PP than Black never smokers (β=1.01 mm Hg, P=0.028). White consistent smokers had similar systolic BP, but lower diastolic BP (β=−2.27 mm Hg, P<0.001) and higher PP (β=1.59 mm Hg, P<0.001) compared with White never smokers. There were no differences in systolic BP, diastolic BP, or PP between Black or White long‐term former smokers compared with never smokers (all P>0.05). CONCLUSIONS: Although the associations of cigarette smoking with alterations in BP are small, the greater PP observed in consistent smokers may contribute in part to the higher cardiovascular disease risk observed in this group because PP is a strong predictor of cardiovascular disease risk after middle age.